Sending the right signal: Notch and stem cells. - Perdigoto, C.N.; Bardin, A.J. (Biochimica et Biophysica Acta, 2013)
Notch signaling plays a critical role in multiple developmental programs and not surprisingly, the Notch pathway has also been implicated in the regulation of many adult stem cells, such as those in the intestine, skin, lungs, hematopoietic system, and muscle.In this review, we will first describe molecular mechanisms of Notch component modulation including recent advances in this field and introduce the fundamental principles of Notch signaling controlling cell fate decisions. We will then illustrate its important and varied functions in major stem cell model systems including: Drosophila and mammalian intestinal stem cells and mammalian skin, lung, hematopoietic and muscle stem cells.The Notch receptor and its ligands are controlled by endocytic processes that regulate activation, turnover, and recycling. Glycosylation of the Notch extracellular domain has important modulatory functions on interactions with ligands and on proper receptor activity. Notch can mediate cell fate decisions including proliferation, lineage commitment, and terminal differentiation in many adult stem cell types. Certain cell fate decisions can have precise requirements for levels of Notch signaling controlled through modulatory regulation.We describe the current state of knowledge of how the Notch receptor is controlled through its interaction with ligands and how this is regulated by associated factors. The functional consequences of Notch receptor activation on cell fate decisions are discussed. We illustrate the importance of Notch's role in cell fate decisions in adult stem cells using examples from the intestine, skin, lung, blood, and muscle. This article is part of a Special Issue entitled Biochemistry of Stem Cells.